Enhancing the Affordability of Cognitive Behavioral Therapy for Children - Al-smadi , Mohammad Shaban; Bakar, Norsuhaily Abu (International Journal of Psychosocial Rehabilitation, 2020)
A new child’s birth brings with its adjustments to the family’s structure and adds up to the parents ’ obligations. Parents want an ideal healthy child. Furthermore, the reverse happens in which families seem to have a disabled child that can impact the family, resulting in the distress of parents from psychological stress that needs professional assistance from experts and therapy. The main purpose of this paper is to investigate the influence of CBTFD on children’s mothers with cerebral palsy and to assess the most useful and effective approach to cope with stress. The researcher conducted research focused on quantitative data to achieve the research goals. This research involved a quasi-experimental approach to research in which the participants collected quantitative data to conclude the findings of the research. The Mann-Whitney results of CBTFD showed that Pre-experimental and Pre-control CBTFD of the pre-distribution specifically mothers of children with cerebral palsy (U = 34.25, z = -5.621, p = 0.000, r = 0.564), experimental and control of the post-distribution (U = 45.00, z = -7.100, p = 0.000, r = 0.714), and the Post-experimental and Post-control (U = 17.00, z = -8.330, p = 0.000, r = -0.837). When comparing the results of all three questionnaire distributions, it was clear that in the experimental group, mothers of children with cerebral palsy performed much better than those in the control group. By analysing the differences between groups, the results of using the Wilcoxon Signed-Rank test revealed that there was a significant difference in the experimental group before, after and after exposure to the program while the insignificant difference observed for the control group. Also, the program is an important intervention in children with cerebral palsy for behavioral problems. The government also recommended to get more training sessions, use the participatory interaction as a-of-class assignment, and monitor the process closely.